Fourteen new species of the genus Nesamblyops Jeannel (Coleoptera: Carabidae: Anillini) from the South Island of New Zealand with redescription of the genus and description of a new subtribe - Sokolov, Igor M. (Zootaxa, 2023)
Fourteen new species of flightless litter ground beetles of the tribe Anillini, genus Nesamblyops, from the South Island of New Zealand, are described. The only hitherto described species from the South Island, Nesamblyops subcaecus (Broun), is similar to the new species from Southland, N. viator n. sp. (type locality: New Zealand, South Island, Fiordland, Resolution Island), based on the structure of male genitalia. The species assembly inhabiting the northwest corner of the South Island comprises two partly sympatric groups composed of three related allopatric species each. The first group includes N. canaanensis n. sp. (type locality: New Zealand, South Island, Nelson, Abel Tasman National Park, Canaan area), N. hobbit n. sp. (type locality: New Zealand, South Island, Nelson, Kahurangi National Park, Mt Domett), and N. ovipennis n. sp. (type locality: New Zealand, South Island, Nelson, Kahurangi National Park, Mt Arthur). The second group represents another lineage and contains N. rotundicollis n. sp. (type locality: New Zealand, South Island, Nelson, Kahurangi National Park, Onekaka area), N. solitarius n. sp. (type locality: New Zealand, South Island, West Coast, western foothills of Victoria Range, Capleston area), and N. subrufus n. sp. (type locality: New Zealand, South Island, West Coast, Upper Buller Gorge, Dublin Terrace). Three additional species known from the northwest corner of the South Island, based on the structure of male genitalia, are unrelated to each other and remaining species of the region. These are N. karamea n. sp. (type locality: New Zealand, South Island, West Coast, Kahurangi National Park, the Karamea River Gorge area), N. montanus n. sp. (type locality: New Zealand, South Island, Nelson, Kahurangi National Park, Lake Sylvester area), and N. kuscheli n. sp. (type locality: New Zealand, South Island, Nelson, Kahurangi National Park, Mt Arthur). The latter species is presumably closely related to the species from the central parts of the West Coast, N. moorei n. sp., (type locality: New Zealand, South Island, West Coast, Ngahere area, Mawhera Forest). Additionally, the central part of the West Coast is inhabited by a small group of two species, N. disjunctus n. sp. (type locality: New Zealand, South Island, West Coast, E slope of the Paparoa Range, Fletcher Creek area), and N. victoriae n. sp. (type locality: New Zealand, South Island, West Coast, Victoria Range, Capleston area). According to the structure of the male genitalia, this group represents a separate lineage within the genus. The most unusual structure of male genitalia belongs to a species without eyes, a trait previously unknown in Nesamblyops, N. magnificus n. sp. (type locality: New Zealand, South Island, Coastal Otago, Allison Conservation Area) that inhabits the southeast corner of the South Island. Digital images of habitus, body parts, drawings of genitalia, as well as distribution maps are provided for all described species. Morphological evidence of the isolated position of Nesamblyops within the tribe Anillini is discussed, with a focus on the morphological comparison of Nesamblyops with the members of Anillini, Tachyini, Bembidiini, Zolini, and Sinozolini, and on the data of published molecular analyses. A new subtribe for the representatives of the genus, Nesamblyopina, n. subtr., is proposed; the newly discovered morphological characters have been incorporated in the redescription of the genus.